1883 R.I. Acts 157, ch. 374, § 1 - (:unkn) unknown (General Publisher, 1883)
No person shall sell to any child under the age of fifteen years, without the written consent of a parent or guardian of such child, any cartridge or fixed ammunition of which any fulminate is a component part, or any gun, pistol or other mechanical contrivance arranged for the explosion of such cartridge or of any fulminate.
--
Keywords: TRANSFER - MINORS